1997
DOI: 10.1002/macp.1997.021981112
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS study of supported TiCl4/MgCl2 catalyst

Abstract: Extended X-ray absorption fine structure analysis (EXAFS) has been used to study supported TiCl,/MgCI, catalysts containing 1.8 wt.-% Ti. Adsorbed TiCI, was found to exist on the MgC12 surface as a dimeric complex. The possible structures of dimeric TiC14 complexes on the (100) face of MgCl, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 6 publications
4
40
1
Order By: Relevance
“…Though tetravalent species also has a high activity for propylene polymerization as in group IV metallocene catalysts, TiCl 4 , which is usually situated in an octahedral symmetry on MgCl 2 [31][32][33]64], might be difficult to offer a vacant site for monomer coordination. Here, isobutyl (iBu) or methyl (Me) was employed as the alkyl group, that is, as the growing chain.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though tetravalent species also has a high activity for propylene polymerization as in group IV metallocene catalysts, TiCl 4 , which is usually situated in an octahedral symmetry on MgCl 2 [31][32][33]64], might be difficult to offer a vacant site for monomer coordination. Here, isobutyl (iBu) or methyl (Me) was employed as the alkyl group, that is, as the growing chain.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In analogous to the first-and second-generation TiCl 3 catalysts [29,30], the mononuclear species on the (1 1 0) surface and the dinuclear species on the (1 0 0) surface were respectively assigned as aspecific and isospecific active sites [25]. Although the nuclearity of surface TiCl 4 species has not been experimentally concluded yet [31][32][33], most of DFT studies have agreed on the energetic preference of the TiCl 4 mononuclear species on the (1 1 0) surface [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…TiCl 4 adsorbs on the MgCl 2 (110) surface only as saturated mononuclear species, while it can dimerize on the (100) surface. [4][5][6][7] Busico et al proposed that such dinuclear species was highly isospecific and mononuclear species was aspecific. [8] iii) Time-dependent change of active sites during polymerization.…”
Section: Introductionmentioning
confidence: 97%
“…An extended X-ray adsorption fine structure (EXAFS) analysis for a TiCl 4 /MgCl 2 precatalyst indicated the dinuclear species on the (100) surface, [6] while a recent Raman spectroscopic study on a co-milled TiCl 4 /MgCl 2 pre-catalyst suggested the mononuclear species on the (110) surface. [7] First-principle calculations showed a consistent trend, i.e.. preference of the TiCl 4 mononuclear species on the (110) surface, and that of the TiCl 4 dinuclear species on the (100) surface, which was as stable as the mononuclear species on the same surface, but absolutely less stable than the mononuclear species on the (110) surface.…”
Section: Introductionmentioning
confidence: 99%